2013
DOI: 10.5301/jva.5000143
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Complications of Arteriovenous Fistula Dialysis Access in an Elderly Population

Abstract: Several aspects should be highlighted: pre-operative color-flow duplex scanning, timing of the creation of the AVF and placement of the AVF as distal as possible.The creation of AVF in elderly patients is a choice supported by the opinion that patients with tunneled central venous catheters have higher mortality rates than those with AVF. In summary, choosing vascular access sites to be created in elderly patients is no different than for younger patients-an AVF remains the gold standard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…We found that in the order of survival of AVF—nondominant radial, non‐dominant brachial, dominant radial, and dominant brachial respectively. A distal AVF may have higher survival rates owing to the presence of multiple venous escapes, 16 reduced occurrence of high flow access complications, or due to absence of steal phenomenon 17 . Similar results were seen by Borzumati et al 17 …”
Section: Discussionsupporting
confidence: 59%
“…We found that in the order of survival of AVF—nondominant radial, non‐dominant brachial, dominant radial, and dominant brachial respectively. A distal AVF may have higher survival rates owing to the presence of multiple venous escapes, 16 reduced occurrence of high flow access complications, or due to absence of steal phenomenon 17 . Similar results were seen by Borzumati et al 17 …”
Section: Discussionsupporting
confidence: 59%
“…18 However, other studies have suggested that age does not have an important impact on fistula outcomes. 19-22 In a retrospective study of 658 patients referred for fistula creation, Weale et al 22 assessed the impact of age on functional outcomes and found no difference in primary or secondary patency with radiocephalic and brachiocephalic fistulas in patients less than 65 years of age, 65 to 69 years of age, and those 80 years of age and older. Inconsistency in prior studies may relate to sample size considerations, a preponderance of single-center studies, differences in definitions, and the lack of adequate risk adjustment for other important predictors of fistula outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have focused on standard definitions of usability, and primary and secondary patency of fistulas. 13-21 We opted for a more pragmatic definition of successful fistula creation. The expressed intent of fistula creation is to spare patients of the complications associated with indwelling catheters.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, one study has shown that patients older than 75 years with autogenous vascular access can have patency that is similar to that of younger patients. 4 Notwithstanding current recommendations, there has been a recent trend away from the Fistula First Initiative in the age group older than 80 years, 5 with age being one of the four predictive factors used by Lok et al to predict failure to mature in fistulas. 6 In our center, the patient's age has not been a consideration in the decision to construct arteriovenous hemodialysis access, with the oldest patient to have access surgery aged 94 years.…”
mentioning
confidence: 99%